Educação infantil e hortas convencionais e/ou agroecológicas: confluências e perspectivas sob o olhar das professoras - Bandeira, Viviane Andrade (2022)
In the current context, it is important to be critical, autonomous, and aware of our role as citizens. Therefore, it is increasingly essential that schools, from Early Childhood Education on, provide children with opportunities for their full development, based on an intrinsic connection between body, mind, and spirit. Within this holistic paradigm, urban school gardens can be used as an pedagogical resource to promote several debates such as healthy nutrition, sustainability, and environmental education. In this sense, it has been established the following research question: What are the confluences between Early Childhood Education and conventional and/or agroecological urban school gardens from the point of view of teachers working in Municipal Centers for Early Childhood Education? To this end, an online survey was developed, via the Google Form platform, structured into four sessions: general profile; consumption habits; school gardens in educational practices; agroecological gardens and Early Childhood Education. The Secretariat of Education of the municipality where this research was conducted organizes its network of school units into regions, totaling ten. Forty-one teachers from all regions answered the questionnaire. The data were analyzed using Discursive Textual Analysis, which comprises three steps. The first step involves the process of unitarization, followed by the organization of categories and, finally, the elaboration of metatexts or communication. The analyses indicate that, of all the participating teachers, most recognize the potential of school gardens as a pedagogical resource to stimulate in children the introduction of habits for healthy eating, through discovery, management, and interactions with the various stages of food cultivation. In this sense, it can awaken their curiosity and visual perception, as well as contribute to their psychomotor development. Moreover, from the perspective of environmental education, we identified two categories of approach to the urban gardens: 1) Environmentally Conscious Education, which represents the majority of the results, and 2) Sustainability. Among the confluences between Early Childhood Education and conventional and/or agroecological urban school gardens can be highlighted the promotion of learning from a range of collective actions, focused on the integral development of children. As for the agroecological garden specifically, in addition to environmental and nutrition approaches, it also enables a practice that articulates academic and popular knowledge, with the participation of families and the community surrounding the school, in addition to promoting reflection on the consumption of pesticide-free food.